Sketch Out the Myth of Wisdom and Blessing of Islamic Boarding School - Zainuddin Syarif; Abdul Gaffar (Postgraduate Program, State Institute on Islamic Studies Purwokerto, 2019)
Boarding school culture is a part of Islamic social setting that acknowledges the differences of human